Evaluating Learning Motivation as a Mediator Between Family Environment and Academic Achievement: Evidence from Indonesian Secondary Students - Maksum, Muh. Nur Rochim; Ihsan, Muhammad Zidan Nur; Vambudi, Viky Nur; Rifai, Alfan; Nisa, Athia Tamyizatun; Alauddin, Muhammad Badat; al Irfani, Sofiy Zaini (FKIP Universitas Lampung, 2025)
Evaluating Learning Motivation as a Mediator Between Family Environment and Academic Achievement: Evidence from Indonesian Secondary Students. Objective: This study aims to investigate the role of motivation as a mediating factor in the relationship between family environment and academic achievement in the Indonesian context. Previous studies have examined the relationships between family environment and academic achievement, as well as the connection between learning motivation and academic achievement. However, based on a literature review, a study investigating the relationship between family environment and academic achievement with learning motivation as a mediating variable has not yet been conducted in Indonesia. Methods: A quantitative approach using Structural Equation Modeling (SEM) was applied to a sample of 156 students from a junior high school in West Java. Results: The results show a significant effect of family environment on learning motivation (β: 0.502, p < 0.001), and a significant effect of learning motivation on academic achievement (β: 0.276, p = 0.030). However, the effect of family environment on academic achievement was not significant, confirming the full mediation of learning motivation. However, the influence of the family environment on learning achievement is not significant, as evidenced by the full mediation of learning motivation (Indirect Effect: 0.129, p = 0.046). Therefore, educational interventions that combine family awareness and student engagement strategies are necessary to help students achieve satisfying academic performance in school. Conclusion: Although the family is the primary environment in the process of student growth and development, its influence on learning achievement occurs indirectly. This influence becomes significant only when the family environment fosters students' motivation to learn. Educational interventions need to strategically integrate increased awareness and the active role of the family with programs to strengthen students' learning motivation, as motivation is a key link between family support and academic success. Keywords: learning motivation, family environment, academic achievement, students.